Multivariate analysis of glycogenes reveals coordinated regulation of immunoglobulin glycosylation in an immortalized human B cell system - Wiggins, Christine D; Sangés Ametllé, Marina; Wu, Claire; Boswell, Kristin L; Watkins, Timothy A; Koup, Richard A; Lauffenburger, Douglas A (bioRxiv, 2025)
While neutralizing ability has traditionally been considered the most important antibody function, appreciation has grown for Fc-mediated 'extra-neutralizing' functions, which are shaped by IgG glycosylation. However, there remain fundamental questions as to how B lymphocytes induce and regulate antibody glycosylation and thus functional capability. Understanding how transcriptional and cell state regulation shape glycosylation could reveal levers to tune protective humoral profiles in a disease- and antigen-specific manner. Prior studies have explored a limited panel of glycogenes and measured bulk glycosylation changes. Here, employing an in vitro antigen-specific B cell culture system, we systematically characterize transcriptional and humoral responses to cytokine perturbations. After exposure to a broad panel of cytokines (IL-4, IL-6, IL-10, IL-17, TNFa, IFNg, APRIL, and BAFF) across multiple concentrations and timepoints, transcriptomic profiling and lectin-based IgG glycome assays are employed to associate cytokine stimuli with both glycogene expression and IgG glycosylation. Supervised and unsupervised machine learning models identify cytokine-specific glycogene "signatures" as well as distinct immunoglobulin glycosylation profiles. We find that cytokines induce rapid transcriptional responses, with glycogene signatures outperforming single-gene changes in distinguishing stimulation conditions. We further demonstrate the ability to induce both pro- and anti-inflammatory IgG glycosylation profiles, particularly in terms of IgG galactosylation. This work demonstrates the utility of this system to parse the cytokine-driven regulation of B lymphocyte glycogenes, establishing a framework for dissecting how environmental cues shape antibody glycosylation, with relevance for autoimmune disease, infection, and vaccine responses.